Effects of Exercise Mode on the Oxygen Uptake Kinetic Response to Severe-Intensity Exercise in Prepubertal Children - Machado, Fabiana A. [UNESP]; Guglielmo, Luiz G. A. [UNESP]; Greco, Camila C. [UNESP]; Denadai, Benedito S. [UNESP] (Human Kinetics Publ Inc, 2009)
The objective of this study was to verify the effect of the exercise mode on slow component of VO(2) (VO(2)SC) in children aged 11-12 years during severe-intensity exercise. After determination of the lactate threshold (LT) and peak VO(2) (VO(2)peak) in both cycling (CE) and running exercise (TR), fourteen active boys completed a series of "square-wave" transitions of 6-min duration at 75%Delta [75%Delta = LT + 0.75 X (VO(2)peak-LT)l to determine the VO(2) kinetics. The VO(2)SC was significantly higher in CE (180.5 +/- 155.8 ml . min(-1)) than in TR (113.0 +/- 84.2 ml . min(-1)). We can conclude that, although a VO(2)SC does indeed develop during TR in children, its magnitude is considerably lower than in CE during severe-intensity exercise.